Bank Ownership and Performance - Alejandro Micco; Ugo Panizza; Mónica Ya\~nez (Inter-American Development Bank, Research Department, 2004)
This paper builds a new dataset on bank ownership and bank performance covering approximately 50,000 observations for 119 countries over the 1995-2002 period. The paper then uses the dataset to reassess the relationship between bank ownership and bank performance, providing separated estimations for developing and industrial countries. It is found that, while ownership is strongly correlated with performance in developing countries, that ownership is not correlated with performance in industrial countries. In particular, the paper suggests that state-owned banks operating in developing countries tend to have lower profitability and higher costs than their private counterparts, and that the opposite is true for foreign-owned banks (which tend to be characterized by higher profitability and lower costs). We also find that, in developing countries, the entry of foreign banks plays a useful role by making domestic banks more efficient in terms of overhead cost and spreads, although we do not find any effect on profitability of domestic banks.
Keywords: G21; D21; 330; Banking; Privatization; Ownership; Performance; Bank; Eigentümer; Privatisierung; Unternehmenserfolg; Welt